Structural analysis of prosodic patterns: the case of excessive prolongations in Israeli Hebrew - Silber-Varod, Vered (Revista Leitura, 2014)
This paper proposes a new framework for prosodic pattern analysis, based on the study of excessive prolongation in spontaneous Israeli Hebrew. In order to reveal whether it is a random phenomenon or a predictable prosodic pattern, a multi-layer linguistic analysis was conducted. First, the phenomenon was taken out of its canonical research framework as a type of speech disfluency. Second, its acoustic characteristics were defined, and the phonological environments of these prolongations were accounted for. Finally, prolongations and their interface with the syntagmatic layer were analyzed. The proposed framework can serve as a format for other prosodic patterns as well. DOI: 10.28998/2317-9945.2013v2n52p271-291